El servicio tarifado “taxímetro” y su impacto en los usuarios y taxistas del cantón Loja a partir del año 2014 - Valarezo Aguirre, María Lourdes (2016)
This research work named: TARIFFED TAXIMETER SERVICE AND ITS IMPACT IN USERS AND TAXI DRIVERS FROM LOJA CITY SINCE 2014, has as aim to generate knowledge about tariffed taximeter commercial service in taxis in conventional and executive mode in Loja city; users satisfaction with the use of tariffed taximeter system, the respective improvements in the service; the actions performed by transit municipality authorities after they had received the competence from “Agencia Nacional de Tránsito”, the necessary settlements respect to control, monitoring and tracing to regulate the use of the device. Since some years ago, the taxis’ service in conventional and executive mode has worked without any control respect to fees when applying the taximeter service and the sanctions that rule the taxis’ union, it was supposed to get better income in the taxi transport service. The applied surveys to users and the interviews with taxi unions’ heads allowed determining which the needed changes in the service are, in the same way the problems that happened at the beginning of the device use. At the end of the research work, conclusions and recommendations were put into consideration of, so that authorities can take into account for future decision taking, the same as the actions to improve the taxi service in Loja city.